2011
DOI: 10.1080/10942910903491181
|View full text |Cite
|
Sign up to set email alerts
|

Protective Ability of Ethanol Extracts ofHypericum ScabrumL. andHypericum RetusumAucher Against the Protein Oxidation and DNA Damage

Abstract: Inhibition of protein oxidation and DNA damage by reactive oxygen species (ROS) would confer benefit to living organisms exposed to oxidative stress, because oxidized proteins are associated with many diseases and can propagate ROS-induced damage. In this study, the ability of the ethanol extracts of Hypericum retusum Aucher (HR) and Hypericum scabrum L (HSm) to protect bovine serum albumin (BSA) from oxidation and DNA damage by hydroxyl radical derived from the Fenton system (Fe 3+ /H 2 O 2 /ascorbic acid) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 55 publications
2
12
0
Order By: Relevance
“…ROS are involved in the normal physiology of living organisms. They act as a messenger for signal transduction and also affect gene expression and are also actively involved in the pathogenesis of diseases such diabetes, cancer and neurodegenerative diseases [18]. Significant protective effect of cell proteins (BSA) by RERC as shown in our studies further confirmed that methanolic RERC's are highly anti-oxidatant which protects proteins from ROS attack.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…ROS are involved in the normal physiology of living organisms. They act as a messenger for signal transduction and also affect gene expression and are also actively involved in the pathogenesis of diseases such diabetes, cancer and neurodegenerative diseases [18]. Significant protective effect of cell proteins (BSA) by RERC as shown in our studies further confirmed that methanolic RERC's are highly anti-oxidatant which protects proteins from ROS attack.…”
Section: Discussionsupporting
confidence: 75%
“…The effects of RERC on protein oxidation were carried out according the method described by Kızıl et al [15]. Interactions of the samples were done with BSA protein.…”
Section: Methodsmentioning
confidence: 99%
“…This assumption is in accordance with previous examinations on various Hypericum species, where it was shown that extracts with higher polyphenolic load also exhibited stronger antioxidant effects [24,25]. Similar results were reported for several Hypericum taxa [26][27][28]. Therefore, the differences in the P R values between the two extracts are rather attributed to differences in the total polyphenol concentration and the relative amounts of the various polyphenols.…”
Section: Antioxidant Activitysupporting
confidence: 80%
“…Many publications show the inhibitory eff ects of plant extracts or their components against protein oxidation and DNA damage caused by reactive oxygen species (11)(12)(13). To our knowledge, this is the fi rst study that has investigated the inhibition ability of DNA damage, protein oxidation and lipid peroxidation by ethanol extract of S. marianum seeds in vitro.…”
Section: Introductionmentioning
confidence: 98%